Heroes inciting political unrest: assessing the perception of former militia (PMU) through a list experiment in Iraq - Dai Yamao (Cogent Social Sciences)
This article endeavors to examine the extent to which individuals perceive the Popular Mobilization Units (PMUs), a prominent former militia umbrella organization in Iraq and a typical example of armed semi-non-state actors, as a primary catalyst for political turmoil and its associated issues, drawing insights from the outcomes of a list experiment conducted within the framework of our original survey. Based on the results of the list experiment, it was found that over 41% of Iraqis consider the PMUs to be a source of political turmoil. This tendency was more pronounced among minority groups and residents of the north and west regions. On the other hand, Shias and supporters of Shiite Islamist parties, particularly those aligned with the Fatah Alliance, were less likely to view the PMUs as a problem.